Sustainable Tourism Management Through Community Ecotourism in Tangkahan North Sumatra - Putri Mentari; Ahmad Kodri Fauzi Hasibuan (Outline Publisher, 2026)
This study examined how local community participation influenced the sustainability of ecotourism in Tangkahan, North Sumatra. The purpose of the research was to determine whether stronger involvement of residents could improve environmental protection, social well-being, and economic stability within the destination. A quantitative explanatory design was used to analyze the relationship between community participation and ecotourism sustainability. Data were gathered through structured questionnaires completed by one hundred respondents who were directly engaged in tourism activities, including residents, managers, and visitors. The analysis applied structural equation modeling to assess measurement accuracy and evaluate the strength of the relationship between the variables. The findings showed that community participation had a positive and statistically significant effect on the sustainability of ecotourism. The path coefficient reached 0.542 with a t-value of 7.587 and a probability value below 0.001. The model explained 29.4 percent of the variation in sustainability and demonstrated a strong predictive value, shown by a Q-square score of 0.566 and a large effect size of 0.416. These results indicated that higher levels of involvement from local residents contributed meaningfully to ecological preservation, improved community welfare, and long-term economic benefits. The study concluded that active engagement from the community served as a key factor in strengthening sustainable tourism management in Tangkahan. Encouraging local participation could support conservation efforts and reinforce future development strategies.